Manganese catalyzed selective hydrogenation of cyclic imides to diols and amines. Issue 10 (31st March 2020) - Das, Uttam Kumar; Janes, Trevor; Kumar, Amit; Milstein, David
Abstract : Herein we report the selective hydrogenation of cyclic imides to diols and amines, homogeneously catalyzed for the first time by a complex of an earth-abundant metal, a manganese pincer complex. Abstract : Herein we report the selective hydrogenation of cyclic imides to diols and amines, homogeneously catalyzed for the first time by a complex of an earth-abundant metal, a manganese pincer complex. A plausible catalytic cycle is proposed based on informative mechanistic experiments.